2016
DOI: 10.7120/09627286.25.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Lambs show changes in ear posture when experiencing pain

Abstract: Ear posture, or the frequency of postural changes, may reflect various emotional states of animals. In adult sheep (Ovis aries), the 'forward' ear posture has been associated with negative experiences whereas the 'plane' posture has been associated with positive ones. This study aimed to see whether ear postures related to the experience of pain in lambs. The ear behaviour of four to eight week-old lambs (n = 44) was measured before and after tail-docking using a rubber ring. Each lamb was docked and its behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 31 publications
5
36
2
Order By: Relevance
“…Ear movements have been reported to be exhibited in aversive situations in pigs (26) and sheep (23,27). In lambs, ear movements are also associated with pain (24). Therefore, our data showing more ear movements after docking support the existence of pain.…”
Section: Signs Of Pain and Stress Immediately After The Proceduressupporting
confidence: 64%
See 1 more Smart Citation
“…Ear movements have been reported to be exhibited in aversive situations in pigs (26) and sheep (23,27). In lambs, ear movements are also associated with pain (24). Therefore, our data showing more ear movements after docking support the existence of pain.…”
Section: Signs Of Pain and Stress Immediately After The Proceduressupporting
confidence: 64%
“…To our knowledge, the ear posture of pigs has been reported in negative situations only in one study (4), which found that the time spent with the ears in a backward posture increased after stress (social isolation combined with negative, unpredictable interventions in pigs). Backward ear posture is also a sign of negative emotion in sheep (23) and of pain in sheep and horses [lambs: (24); horses: (25)]. In our study, there was no effect of docking on the backward posture but docked piglets were more often observed with their ears in a posture perpendicular to the head-tail axis.…”
Section: Signs Of Pain and Stress Immediately After The Proceduresmentioning
confidence: 44%
“…Overt demonstration of pain-related behaviour may increase the likelihood that an individual herbivore becomes a target of predation. In these species, pain-related behaviour tends to be very subtle, for example in sheep the position of the ears relative to the head [12]. In hunting carnivores, predation by other animals is less likely and so pain-related behaviour tends to be more overt and easier to detect.…”
Section: Pain Pathways and The Importance Of Cognitionmentioning
confidence: 99%
“…For example, Guesgen et al have recently explored how sheep use their ears to express pain and have developed a 'lamb grimace scale' to characterize the facial expression sheep use to communicate pain to other sheep. 30 This information adds to the growing body of knowledge about facial expressions in animals and their value in social communication.…”
Section: Innovative Behavioural Techniques For Exploring Animal Emotimentioning
confidence: 99%